THE PROFILE OF ARGUMENTATION SKILL USING âTOULMIN ARGUMENTATION PATTERNâ ANALYSIS IN THE ARCHIMEDES PRINCIPAL ON THE STUDENTS OF SMA KOTA BANDAR LAMPUNG - -, Viyanti (Jurnal Pendidikan IPA Indonesia, 2015)
This research aims to indentify studentâs argumentation skill which is seen from argumentation discourse and then it is analyzed using TAP (Toulmin Argumentation Pattern) which consists of some components such as data, claim, warrant, backing and rebuttal on the topic of Archimedes Principle. The method used in this research is descriptive method. The result of this research shows based on the written assignment, the studentâs scientific argumentation skill is not good. The student often do not use an appropriate argumentation, do not use adequate evidence, or try to straighten their own option or try to apply their own argument.